Oxidation state and metasomatism of the lithospheric mantle beneath the Rae Craton, Canada: strong gradients reflect craton formation and evolution - Alan B. Woodland; Carolin Gräf; Theresa Sandner; Heidi E. Höfer; Hans-Michael Seitz; D. Graham Pearson; Bruce A. Kjarsgaard (Scientific Reports, 2021)
Abstract We present the first oxidation state measurements for the subcontinental lithospheric mantle (SCLM) beneath the Rae craton, northern Canada, one of the largest components of the Canadian shield. In combination with major and trace element compositions for garnet and clinopyroxene, we assess the relationship between oxidation state and metasomatic overprinting. The sample suite comprises peridotite xenoliths from the central part (Pelly Bay) and the craton margin (Somerset Island) providing insights into lateral and vertical variations in lithospheric character. Our suite contains spinel, garnet-spinel and garnet peridotites, with most samples originating from 100 to 140 km depth. Within this narrow depth range we observe strong chemical gradients, including variations in oxygen fugacity (ƒO2) of over 4 log units. Both Pelly Bay and Somerset Island peridotites reveal a change in metasomatic type with depth. Observed geochemical systematics and textural evidence support the notion that Rae SCLM developed through amalgamation of different local domains, establishing chemical gradients from the start. These gradients were subsequently modified by migrating melts that drove further development of different types of metasomatic overprinting and variable oxidation at a range of length scales. This oxidation already apparent at ~ 100 km depth could have locally destabilised any pre-existing diamond or graphite.